2020
DOI: 10.1016/j.jor.2019.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

Patient reported outcome measures of bilateral reverse total shoulder arthroplasty compared to bilateral anatomic total shoulder arthroplasty

Abstract: The purpose of this study was to compare patient reported functional outcomes following bilateral aTSA vs rTSA. A retrospective review was conducted on twenty-six pateints who underwent staged bilateral aTSA or rTSA, with a minimum of 2 years follow up. Thirteen patients were included in each group, and patient assessed functional outcomes were measured using the PENN Score, ASES, SST, and SF-12. No statistically significant differences were found between the two groups for all functional outcome scores, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Only three studies [ 10 , 16 , 17 ], which are retrospective, met the inclusion criteria and were included in the meta-analysis. It involved 86 subjects in the bTSA group and 43 subjects in the bRSA group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies [ 10 , 16 , 17 ], which are retrospective, met the inclusion criteria and were included in the meta-analysis. It involved 86 subjects in the bTSA group and 43 subjects in the bRSA group.…”
Section: Resultsmentioning
confidence: 99%
“…However, another study comparing bRSA to bTSA showed that even though the latter had better postoperative functional outcomes, the difference between the pre- and postoperative scores was not significantly different [ 16 ]. Higher postoperative functional scores in bTSA might be explained by the higher baseline function, which may be a result of the different indications in the analyzed studies, such as the presence of OA in the bTSA group or the presence of rotator cuff tear arthropathy or TSA revision in the bRSA group [ 10 , 16 - 18 ], and the older age of patients receiving bilateral reverse implants [ 10 , 16 , 17 ]. In fact, there was no difference in postoperative pain or adverse events between these two implants and studies have reported similar levels of satisfaction [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%